Missed Officer–Probationer Contacts and Its Influence on Rearrest - Zettler, Haley R. (Criminal justice policy review, 2020)
Probation supervision is marked by the dual roles of surveillance and casework. A key feature of supervision that aligns with the goals of community safety through surveillance is the use of officer-probationer contacts. The current study explores the relationship between missed probation contacts and rearrest while on supervision in a surveillance-driven context. Logistic regression analyses modeled the effects of missed contacts on rearrests using probation data from a large supervision agency (n = 3,809). Analyses included the overall percentage of missed contacts and missed contacts above/below the median and mean percentage of missed contacts to subsequent rearrests while on supervision. Overall, the percentage of missed contacts increased the likelihood of rearrest while on probation. Furthermore, the percentage of missed probation contacts that significantly predicted rearrest was lower than expected (4.17%). The results suggest that missing contacts while on probation has a negative impact on probation success. Implications of these findings are discussed.